Effects of Carbon Fiber Compression Ratio and Electrolyte Flow Rate on the Electrochemical Performance of Vanadium Redox Batteries. (11th March 2021) - Tai, Zhongxu; Hanawa, Kenzo; Ju, Dongying; Luo, Wenping; Lyu, Rui; Ishikawa, Kousuke; Sato, Susumu
Abstract : All-vanadium flow batteries (VRFBs) are used in the field of energy storage due to their long service life and high safety. In order to further improve the charge-discharge performance of VRFB, this study mainly used the comparative evaluation of VRFB's carbon fiber electrode compression ratio and electrolyte flow rate. The battery is charged and discharged under different current densities, different compression ratios, and different flow rates. The results show that increasing the compression ratio at different current densities can reduce the internal resistance of the battery, but an excessive compression ratio will accelerate the transfer of vanadium ions, increase the deviation of the electrolyte, and reduce the Coulombic efficiency of the battery. The performance of the battery tends to be balanced when the compression ratio is 30%. At the same time, in the case of the same compression ratio, increasing the flow rate of the electrolyte can reduce the internal reaction resistance of the battery. When the flow reaches a certain value, the influence on the internal resistance will be smaller.